A reconsideration of food insecurity trends in the United States - Gundersen, Craig (Applied Economic Perspectives and Policy, 2024)
The food insecurity status of a household in the United States is generally put into the categories of food secure, low food secure, or very low food secure. Substantial differences in the level of need within categories are then ignored. In response, I e
Keywords: Financial Constraints; food Secure; Hunger; Poverty; Food Insecurity